Bella Plus Quam Ciuilia: The Dismantlement of Traditions and the Destruction of Romanitas in Lucan’s Pharsalia - Mackevič, Ana Marija Marija (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English]This article analyzes Lucan’s epic poem Pharsalia, which acquired the title of an “anti-epic” because of its very open rebellion against the genre traditions. This rebellion here is interpreted as an intentional means of expression, consciously chosen in service of the ideological message of the poem. The construction of the message relies largely on the distortion of the traditional motives of the epic genre – mostly in reference to the Vergilian model, which had become a default framework for all Roman epics written after it. Vergil’s Aeneid was employed by the Augustan imperial propaganda as a means of emphasizing the connection of the current government to the Roman past and the idea of rehabilitating the mores maiorum after the failure of the late Republic and the unrest of the civil wars. The Pharsalia, on the other hand, being written under (and, as this article argues, in opposition to) the Neronian government, is a reflection of attitudes shared by the Roman upper classes regarding the failure of the newly established empire. Thus, the author, by employing the tropes of the Vergilian model (but distorting them) and giving his audience the inverted version of these traditional elements (while still staying within the traditional framework), is able to underline the ideological conflict he has with the Augustan pro-imperial propaganda. This article examines two traditional epic tropes: one of the virtuous war and one of the individual virtus on the battlefield. The Vergilian virtuous war turns into a suicidal gesture of the main protagonist – the Roman people. This shows a certain distortion of the Republican understanding of romanitas (the Roman people and the Roman state as a unified organism), later undermined by the individualism of the imperial regime. We also see how the individual virtus (which was a large component of romanitas, too) becomes a grotesque and distorted version of itself. The concept of military loyalty and sacrifice for the collective good turns into a tragic furor and blind allegiance to a power-hungry individual. Thus, the state and the collective good are being sacrificed for the individual good in both cases. This is, for Lucan, the root of the sociopolitical issues of his time – the moral degradation and the erasure of traditional Roman values not just in the government, but also in the Roman society as a whole. This sentiment, it is argued, could reflect the overall rejection of the imperial romanitas and a tendency of returning to the traditional Republican concepts in the Roman society of the time, which is to be understood as a reaction to the political and sociocultural state of Rome under Nero.
Keywords: Lucan; Romanitas; Pharsalia; Civil War; national identity; Nero